The Role of Graffiti as an Expression of Youth Identity: (Case Study on ROCE and BKRE Bombers) - Danenin Brenindadini Puspita Puspita (Commsphere: Jurnal Ilmu Komunikasi, 2024)
Graffiti art has drawn pros and cons from the public and is considered a Form of vandalism or crime because it damages public facilities. However, for graffiti artists or bombers, graffiti is a place to express themselves. Even though it received a lot of negative responses from the public, graffiti was able to survive and continue to exist. Based on this, the author wants to know the meaning behind the activities of the bombers who chose graffiti art as a medium of expression. The author uses qualitative research methods. The data collection techniques used in this article are interviews, observation, and documentation. The theory used is the theory of self-expression through the symbolic interaction approach by George Herbert Mead. The research results show that graffiti perpetrators or bombers choose graffiti as a medium for self-expression and self-existence. Graffiti allows bombers to display their work to the broader public. Keywords: Graffiti, Bombers, Self Expression